Inovasi Layanan Rakyat Untuk Sertifikat Tanah (Larasita) Di Kantor Pertanahan Kota Magelang - Azizah, Annisa Kurnia Nur (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
The purpose of this innovation is as written in the regulation of the head of Badan Pertanahan Nasional Republik Indonesia (Indonesian Republic of National Land Registry Department) number 18 in the year of 2009 about LARASITA Badan Pertanahan Nasional Republik Indonesia, to make it easier for the people who has business with land registry office to follow up their business without having to come to the office, and so that the people can get the cost information and express their complaints about the land registry service easily. This research uses descriptive research with quantitative method. The location of this research is in Land Registry Office of Kota Magelang. Data's gathering techniques used are interview and observation techniques. The result of this research showed that LARASITA gives service to the people in land certificate service. The suggestion that can be given is a repairment in the connecting antenna to support the internet access in LARASITA implementation. Keywords: innovation, land certificate, land certificate service, LARASITA